2017
DOI: 10.1002/ccr3.1239
|View full text |Cite
|
Sign up to set email alerts
|

Massive hemorrhage following definitive esophageal chemoradiation: teaching case of a fatal aortoesophageal fistula and lessons learned

Abstract: Key Clinical MessageEsophageal self‐expandable metal stents and radiotherapy are valuable in combination for palliation and definitive treatment of esophageal cancer. However, risk of aortoesophageal fistula is significant in patients with evidence of malignant aortic invasion. Use of thoracic endovascular repair may represent an approach to early intervention in high‐risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Moreover, the high pressure exerted by the stent on the esophageal wall can impede blood supply, leading to localized ischemia, necrosis, or ulceration. Local inflammation and growth of the tumor beneath the stent are also potential contributing factors [34,35]. Hence, it is both reasonable and crucial to recognize previous stent implantation as a reliable predictor of AEF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high pressure exerted by the stent on the esophageal wall can impede blood supply, leading to localized ischemia, necrosis, or ulceration. Local inflammation and growth of the tumor beneath the stent are also potential contributing factors [34,35]. Hence, it is both reasonable and crucial to recognize previous stent implantation as a reliable predictor of AEF.…”
Section: Discussionmentioning
confidence: 99%
“…Возможными причинами возникновения АЭС после стентирования пищевода могут быть: прямое повреждение стенки пищевода и аорты, избыточное давление стента на стенку пищевода и аорты с развитием ее ишемии и последующего некроза, непосредственная инвазия опухоли в аорту и механическое воздействие стента на стенку в результате дыхательных движений и передаточной пульсации [16].…”
Section: Discussionunclassified
“…Endoscopy is the first choice for investigating upper gastrointestinal bleeding, but UGB caused by AEF with esophageal cancer cannot always be diagnosed in a timely manner. There is also a risk of dislodging clots and causing fatal bleeding with endoscopy[ 13 ]. Previous studies have shown that most patients with stable circulation and an aortic gastrointestinal fistula had undergone gastroscopy, but only approximately 25% were diagnosed with an aortic gastrointestinal fistula in time[ 6 ].…”
Section: Discussionmentioning
confidence: 99%